KESIAPSIAGAAN PENGELOLA WISATA DAN PEDAGANG DALAM MENGANTISIPASI BENCANA GEMPA DAN TSUNAMI DI KAWASAN WISATA PANTAI DI KOTA PARIAMAN - Andika Rahman; Triyatno Triyatno (JURNAL BUANA, 2020)
This research aims are understand the preparedness of tourism administrators and the merchants in disaster earthquake and tsunami anticipation at beach tourism area of Pariaman City. The samples of this study are 10 person of tourism administrators and 55 persons of merchants at beach tourist area of Pariaman City. The data of preparedness level of tourism administrator and merchants is collected by distributing the questonnaire for quantitative data. Based on the study result showed that the preparedness related to knowledge of both earthquake and tsunami was categorized as prepared for tourism administrators (76.8%). and for the merchants was categorized as less prepared (70.5%). Related to the plan of emergency response of disaster for tourism administrator was categorized as prepared (74.8%). and for the merchant was categorized as less prepared (66%). Related to warning system of disaster for tourism administrator was categorized as prepared (73.75). and for the merchant was categorized as less prepared (70.2%) Related to the mobillity of resource for tourism administrator was categorized as prepared (73,5%) and less prepared for the merchant (64.3%). Of the four parameters above, it can be denied that the tourism administrator in the prepared category, namely (74.8%), while the merchant preparedness is in the category of less prepared (68.2%), this the training and socializations of earthquake and tsunami disaster preparedness at beach tourism area of Pariaman City is required to be periodically implemented.